The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00432-010-0938-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic growth inhibition in HL-60 cells by the combination of acyclic retinoid and vitamin K2

Abstract: The synergistic effects of ACR and VK(2) on HL-60 cells may provide a novel strategy for treating leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Stained cells were analyzed within 1 hour. Annexin V-FITC-positive and PI-negative cells were counted as apoptotic cells as described previously (29).…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…Stained cells were analyzed within 1 hour. Annexin V-FITC-positive and PI-negative cells were counted as apoptotic cells as described previously (29).…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…[75] Combined treatment with ACR plus valproic acid, a histone deacetylase inhibitor, also acts synergistically to induce apoptosis and G 0 –G 1 cell cycle arrest in HCC cells by inhibiting phosphorylation of RXRα, ERK, Akt, and glycogen synthase kinase-3β proteins. [53] In addition to HCC, in both human pancreatic cancer and leukemia cells,[6676] the combination of ACR plus gemcitabine or vitamin K 2 synergistically inhibits cell growth and induces apoptosis by inhibiting Ras activation and RXRα phosphorylation. Moreover, induction of nuclear receptors that dimerize with RXR, such as RAR and PPAR,[7778] and recruitment of their ligands also exert synergistic growth inhibition in cancer cells when combined with ACR.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, loss-of-function experiments using chemical inhibitors indicated that the growth-suppression effect of VK2 derivatives was mediated by caspase/transglutaminase-related signaling pathways, which are underlie the cancer-selective cell death induced by ACR in HCC cells (15). Indeed, synergistic growth inhibition by ACR and VK2 in combination has been reported in the human promyelocytic cell line HL60 (28) and HCC cell line Huh7 (29) by virtue of sharing a similar side chain structure. However, the IC50 values of VK2 derivatives are more than 20 mm (Fig.…”
Section: Discussionmentioning
confidence: 99%